Educational Policy and Educational Practice - McLaughlin, Milbrey W.; Center for Research on the Context of Secondary School Teaching ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Cycles of educational reform initiatives and their effects on practice are reviewed in this paper, which focuses on the relationship between state and federal policy and local practices. The first part discusses the first generation of reform that began with the passage of the 1965 Elementary and Secondary Education Act. Such reforms were generally redistributive and categorical, resulting in changes in the context of educational practice and in a separation between governance and instruction. Second-generation reform policies, which featured the states, are discussed next. The two waves within this second era focused on state regulation of instruction and practice and on issues of professionalism and local responses, respectively. Different objectives, notions of the "problem," assumptions about policy solutions, and social/political contexts characterize each generation of educational policy. A conclusion is that the complexity of teaching practice prevents generalized, consistent change by policy. (31 references) (LMI)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: G0087C235.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Change; Educational Policy; Elementary Secondary Education; Governance; Instructional Effectiveness; Instructional Improvement; Policy Formation; School Restructuring; State Action; Opinion Papers